2022
DOI: 10.1021/acsomega.2c03606
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Study of Seawater-Based Fracturing Fluid Containing Polymer, Crosslinker, and Chelating Agent

Abstract: Freshwater is usually used in hydraulic fracturing as it is less damaging to the formation and is compatible with the chemical additives. In recent years, seawater has been the subject of extensive research to reduce freshwater consumption. The study aims to optimize the rheology of seawater-based fracturing fluid with chemical additives that reduce the formation damage. The studied formulation consists of a polymer, a crosslinker, and a chelating agent to reduce seawater hardness. We used a standard industry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…SW and Na 2 SO 4 were not stable and had much lower viscosity compared to the other solutions. Similar results of DI and SW were achieved in a similar study . From the figure, it can be concluded that Na 2 SO 4 is the source of viscosity reduction of the SW.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SW and Na 2 SO 4 were not stable and had much lower viscosity compared to the other solutions. Similar results of DI and SW were achieved in a similar study . From the figure, it can be concluded that Na 2 SO 4 is the source of viscosity reduction of the SW.…”
Section: Resultsmentioning
confidence: 99%
“… Dissolvine StimWell DGH GLDA structure—GLDA-Na 4 . 22 Reprinted with permission from ref ( 22 ) Copyright 2022, American Chemical Society. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second section examines the impact of varying concentrations of GLDA on the crosslinked polymer. The research was done by selecting just two concentrations (4 and 10 wt %) since the very high concentration had a detrimental effect based on our previous study . Finally, the optimized GLDA concentration was tested with the crosslinked polymer at different temperatures.…”
Section: Methodsmentioning
confidence: 99%
“…The CMHPG cationic polymer employed in these tests as a gelling agent has previously shown positive results when hydrated in DI and SW. 26 When the chain of CMHPG polymers absorbs water, it transforms from a compacted state to an extended-relaxed state named hydration. Since CMHPG hydrates quicker, is more stable at low pH, and degrades more slowly than competing polymers, it has widespread usage in fracturing fluids.…”
Section: Methodsmentioning
confidence: 99%